Promoting Individual and Collective Creativity in Science Students. (September 2020) - Reche, Isabel; Perfectti, Francisco
Abstract : Creativity is a scientific skill necessary to develop a successful research career. We expose the importance of a growth mindset, divergent, lateral, and associative thinking, serendipity, and being part of a nonhierarchical and diverse research team to improve both individual and collective creativity.